Dupilumab and the potential risk of eosinophilic pneumonia: case report, literature review, and FAERS database analysis - Zhou, Xiyuan; Yang, Ge; Zeng, Xuemei; Wang, Lan; Xiang, Jing; Zhao, Jinyu; Chen, Xuejun; Zhang, Lixia (Frontiers in Immunology, 2024)
Eosinophilic pneumonia (EP) is a rare but noteworthy adverse effect linked to Dupilumab, an IL-4 and IL-13 inhibitor used in the managing atopic diseases. The underlying mechanisms, potential predisposing factors, clinical characteristics, and optimal management strategies for Dupilumab-induced EP remain unclear. We report a 71-year-old patient who developed acute eosinophilic pneumonia (EP) after the first 600 mg dose of dupilumab. EOS were also transiently increased (up to 1600 cells/μl).After the acute EP was effectively treated with glucocorticoids, dupilumab treatment was continued. Rash, itching, and immunoglobulin E levels continued to decrease in the patient, and no further pulmonary adverse events occurred. We combined this case with a literature review of nine articles and analyzed data from 93 cases reported in the FAERS database of patients developing EP after Dupilumab use. Our findings implies that Dupilumab may induce EP, particularly in individuals over 45 years old, those with a history of respiratory diseases, and those who have previously used inhaled or systemic steroids. Vigilance is required, especially when there is a persistent elevation in peripheral blood eosinophils during treatment. While steroid treatment can effectively manage EP, more data is needed to determine the safety of resuming dupilumab treatment after controlling pneumonia.